Phlorotannin-Rich Ascophyllum nodosum Seaweed Extract Inhibits Influenza Infection - Daniele F. Mega; Parul Sharma; Anja Kipar; Udo Hetzel; Chloe Bramwell; Alan Merritt; Samuel Wright; Chris Plummer; Richard A. Urbanowicz; James P. Stewart (Viruses, 2024)
Seaweed-derived compounds are a renewable resource utilised in the manufacturing and food industry. This study focuses on an enriched seaweed extract (ESE) isolated from Ascophyllum nodosum. The ESE was screened for antiviral activity by plaque reduction assays against influenza A/Puerto Rico/8/1934 H1N1 (PR8), A/X-31 H3N2 (X31) and A/England/195/2009 H1N1 (Eng195), resulting in the complete inhibition of infection. Time of addition assays and FACS analysis were used to help determine the modes of action. The therapeutic potential of ESE was then explored using differentiated human bronchiole epithelial cells at the air–liquid interphase and a murine model challenged with IAV. The data indicates that ESE primarily interacts directly with virions, reducing mean virus–cell binding by 79.3% with 0.01 mg/mL ESE. Interestingly, ESE also inhibits the early and late stages of the influenza A lifecycle when treatment occurs after cell binding. This inhibitory effect appears to reduce the internalisation of the virus and the release of progeny virus by targeting neuraminidase activity, with IC50 values of 0.5 μg/mL for X31, 3.2 μg/mL for Eng195 and 12.8 μg/mL for PR8. The intranasal administration of 5 mg/kg ESE in mice infected with IAV reduced the viral load in lung tissue. ESE may be a promising broad-acting antiviral agent in the treatment of influenza infections.